2021
DOI: 10.18632/aging.203755
|View full text |Cite
|
Sign up to set email alerts
|

Functional rare variant in a C/EBP beta binding site in NINJ2 gene increases the risk of coronary artery disease

Abstract: Objective: NINJ2 regulates activation of vascular endothelial cells, and genome-wide association studies showed that variants in NINJ2 confer risk to stroke. However, whether variants in NINJ2 are associated with coronary artery disease (CAD) is unknown. Methods: We genotyped rs34166160 in NINJ2 in two independent Chinese GeneID populations which included 2,794 CAD cases and 4,131 controls, and performed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Sequencing of MEF2A exon 11 revealed a rare 21-bp deletion in five CAD patients, indicating that this deletion might be a specific cause of CAD [44]. Wang et al genotyped the rare variant rs34166160 in NINJ2 and demonstrated that rs34166160 significantly confers risk of CAD [45].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of MEF2A exon 11 revealed a rare 21-bp deletion in five CAD patients, indicating that this deletion might be a specific cause of CAD [44]. Wang et al genotyped the rare variant rs34166160 in NINJ2 and demonstrated that rs34166160 significantly confers risk of CAD [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several genomic variants have been associated to date with either risk or severity of PAH, 58 but the mechanisms underlying these associations, particularly those involving the common noncoding variants, are poorly understood. 59 In the case of the tag SNP rs2856830, 60 we investigated associated SNPs, determined functional capacity 61 of those SNPs, and identified differentially binding transcription factors. In doing so, we defined the pathogenic genomic architecture containing SNP rs9277336 including allele‐specific binding of ACTN4 and identified targets that can drive PAH pathogenesis, explaining the association between this genetic locus and PAH outcomes 62 (Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPCR ligand binding [60], extracellular matrix organization [61], cytokine signaling in immune system [62], interferon signaling [63], signaling by GPCR [64], neuronal system [65] and platelet activation, signaling and aggregation [66] plays an important role in the schizophrenia. Studies have revealed that SIX1 [67], VIP (vasoactive intestinal peptide) [68], GATA6 [69], FRZB (frizzled related protein) [70], CD40 [71], WT1 [72], PCDHGA3 [73], TFAP2B [74], HFE (homeostatic iron regulator) [75], NKX2-5 [76], IGFBP7 [77], HLA-F [78], CCL2 [79], COL1A2 [80], RUNX1 [81], TFF3 [82], IRX4 [83], NOS1 [84], DKK2 [85], IL18R1 [86], ADAM12 [87], NPPC (natriuretic peptide C) [88], COL1A1 [89], ABCG2 [90], SIX2 [91], CSRP1 [92], MR1 [93], NINJ2 [94], ACE (angiotensin I converting enzyme) [95], TBX1 [96], CTSC (cathepsin C) [97], DLX6 [98], KCNE1 [99], AZGP1 [100], CYP1B1 [101], PRRX1 [102], CD34 [103], A2M [104], CDKN2A [105], SERPINE1 [106], CD44 [107], FABP4 [108], ITGB3 [109], ALOX5AP [110], DAND5 [111], SFRP4 [112], RUNX2 [113], TACR3 [114], MYD88 [115], CYBA (cytochrome b-245 alpha chain) [116], STAT6 [117], FOXC1 [118], FN1 [119], TLR6 [120], CAV1 [121], RGS4 [122], TPM2 [123], TNFSF4 [124], LOX (lysyl oxidase) [125], SMOC2 [126], SPHK1 [127], FOLH1 [128], CYP2C8 [129], CD163 [130], DIRAS3 [131], OSMR (oncostatin M receptor) [132], POSTN (peri...…”
Section: Discussionmentioning
confidence: 99%